A Novel Highly Sensitive Humidity Sensor Based on ZnO/SBA‐15 Hybrid Nanocomposite. Issue 12 (31st August 2015) - Tomer, Vijay K.; Duhan, Surender; Malik, Ritu; Nehra, Satya P.; Devi, Sunita
Abstract : This work deals with the study of hydrothermally synthesized zinc oxide (ZnO) loaded mesoporous SBA‐15 hybrid nanocomposite for relative humidity sensing (RH) at room temperature. The sensor exhibits an excellent ~5 orders impedance change along with excellent linearity, quick response time (17 s), rapid recovery time (18 s), negligible hysteresis (1.2%), good repeatability, and stability (1.8%) in 11%–98% RH range. In addition, complex impedance spectra of the sensor at different RHs were analyzed to understand the humidity sensing mechanism. Our study can open a new way for realizing ZnO/SBA‐15 hybrid nanocomposite for fabrication of high‐performance RH sensors.